2020
DOI: 10.1177/0022042620974076
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Assessment of Stigma in Law Enforcement Officers’ Responses to Opioid Overdoses

Abstract: Prior work has suggested that provider-based stigma of substance use disorders may be one barrier to fighting the opioid epidemic. However, to date, provider-based stigma has been afforded little attention in the context of the criminal justice system. The goal of the current study was to extend this line of research by examining the impact of provider-based stigma toward opioid using persons to beliefs about help that should be provided to persons experiencing an overdose among a sample of 208 police officers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This included attempts to minimize role conflicts that might contribute to or perpetuate stigmatizing attitudes or beliefs or feelings of compassion fatigue among team members based on their professional affiliation (Carroll et al, 2020;Kruis & Merlo, 2021). Specifically, interviewees reported that the clinician took the lead when interacting with overdose survivors and family members and that the LEO and medic supported the interaction as needed and as directed.…”
Section: Discussionmentioning
confidence: 99%
“…This included attempts to minimize role conflicts that might contribute to or perpetuate stigmatizing attitudes or beliefs or feelings of compassion fatigue among team members based on their professional affiliation (Carroll et al, 2020;Kruis & Merlo, 2021). Specifically, interviewees reported that the clinician took the lead when interacting with overdose survivors and family members and that the LEO and medic supported the interaction as needed and as directed.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found police discretion may be shaped by many factors including officer age, race, and rank (Beyer et al, 2002 ), police culture (Barberi & Taxman, 2019 ), suspect characteristics and demeanor, and the nature of the offense (Brown et al, 2009 ; Engel, et al, 2018 ; Novak & Engel, 2005 ). Studies have found that police believe people who use drugs will not hesitate to lie, lack willpower, are dangerous to be around, and cannot be trusted in situations such as child care (del Pozo et al, 2021 ; Kruis et al, 2020 ; Kruis & Merlo, 2020 ); in general they evince the stigma toward people who use drugs found in the general population.…”
Section: Discussionmentioning
confidence: 99%
“… 49 None of the police officers in this sample had administered naloxone, so the perspectives of this stakeholder group may be shaped by their distinct role at overdose events. As police are increasingly asked to transition their focus toward providing linkages to treatment and promoting overdose awareness in response to the opioid crisis, 50 , 51 research examining best practices for training police officers on overdose response is critical. 34 Whether police officers’ and other emergency personnel's perspectives are related to their frequencies of overdose response is also worth additional exploration.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Whether police officers’ and other emergency personnel's perspectives are related to their frequencies of overdose response is also worth additional exploration. 51 , 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation